Mesoporous composite material as well as preparation method and application thereof

By preparing the spherical egg yolk eggshell structure of mesoporous composite material, the core is metal phosphate and the outer shell is mesoporous silica, the problem of poor selectivity for rare earth ion adsorption in the prior art is solved, and efficient recycling and separation of low-concentration rare earth wastewater is achieved.

CN120325261APending Publication Date: 2025-07-18GANJIANG INNOVATION ACAD CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510508992.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-22
Publication Date
2025-07-18

AI Technical Summary

Technical Problem

It is difficult for existing adsorption materials to achieve efficient selective adsorption and resource recycling of low-concentration rare earth ions in complex and high-concentration interference ion environments.

Method used

The spherical egg yolk eggshell structure using mesoporous composite material, the core is metal phosphate and the outer shell is mesoporous silica, forming a spherical egg yolk eggshell structure in a cavity. By controlling the preparation process parameters such as raw material ratio and calcining atmosphere, the specific surface area and active sites are improved, and the nano-domain effect is enhanced.

Benefits of technology

It has achieved high adsorption rate and high selectivity for rare earth ions in low-concentration rare earth wastewater, especially for Sm3+ and Eu3+, adapted to complex interfering ion environments, and was suitable for efficient recycling of rare earth wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120325261A_ABST
    Figure CN120325261A_ABST
Patent Text Reader

Abstract

The invention relates to a mesoporous composite material and a preparation method and application thereof.The mesoporous composite material is of a spherical egg yolk eggshell structure, the spherical egg yolk eggshell structure comprises an inner core, a shell located outside the inner core and a cavity formed between the inner core and the shell, the inner core comprises metal phosphate, and the outer shell comprises metal oxide. The shell comprises mesoporous silica; the mesoporous composite material is regular in morphology and adjustable in structure, has a nano confinement effect and rich active sites, is high in specific surface area, has a high-selectivity adsorption effect on Sm < 3 + > and Eu < 3 + > in a rare earth solution with a large number of interference ions, and has a relatively good application prospect in extraction and separation of various rare earth ions in rare earth-containing wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of rare earth resource recovery, and particularly relates to a mesoporous composite material, a preparation method thereof, and an application thereof. Background Art

[0002] Rare earth elements are known as "industrial vitamins" and can be used as important raw materials in fields such as fluorescent lasers, new energy materials, special alloys, and electronic information, and are widely used in high-tech fields such as aerospace and national defense. Since mine tail water containing low-concentration rare earths will still seep out for a long time after in-situ leaching mining, a large amount of waste water containing low-concentration rare earths such as extraction and precipitation will also be generated in rare earth separation plants. The discharge of these waste waters will not only cause environmental pollution but also result in waste of rare earth resources. With the continuous growth of the global demand for rare earth resources, studying the efficient adsorption and recovery of low-concentration rare earths from waste water is not only beneficial to environmental protection but also can alleviate the rare earth supply crisis, and has important environmental and economic benefits.

[0003] Currently, the methods for enriching and recovering low-concentration rare earth ions mainly include physical methods, chemical methods, and biological methods. Physicochemical methods include reverse osmosis, extraction, adsorption, ion exchange, precipitation, etc. Among them, the adsorption method has received extensive attention and research due to its advantages such as simple operation, large treatment capacity, low energy consumption, and recyclability of the adsorbent. Currently, commonly used traditional adsorbents mainly include zeolite, clay, activated carbon, montmorillonite, chitosan, fly ash, and lignin, etc. However, traditional adsorption materials have problems such as small specific surface area, low adsorption force, slow adsorption rate, and poor selectivity; moreover, the rare earth concentration in waste water is low, and there are a large number of impurity ions such as iron, aluminum, and lead. It is difficult for traditional adsorption materials to achieve efficient selective adsorption and resource recovery of low-concentration rare earth ions. Therefore, providing a new type of adsorption material for achieving efficient selective adsorption of low-concentration rare earth ions and a preparation method thereof is one of the technical problems that need to be solved urgently at present.

[0004] CN115672293A discloses a sodium alginate-loaded clay mineral gel microsphere, a preparation method thereof, and an application as a rare earth ion adsorption material. The clay mineral is dispersed in water to form a clay mineral suspension; sodium alginate is added to the clay mineral suspension, stirred, and then a pore-forming agent is added and stirred evenly, and then dropped into a calcium ion solution for cross-linking reaction to form gel microspheres. The gel microspheres are washed and dried to obtain the sodium alginate-loaded clay mineral gel microspheres. This patent has certain applications in the field of rare earth separation, but it is difficult to achieve selective separation of rare earth elements.

[0005] CN115970660A discloses a composite adsorbent for rare earth recovery and its preparation method. Using methyl methacrylate as a monomer, it is mixed with modified earthy graphite for functionalization transformation, and a composite adsorbent for rare earth recovery is prepared under certain conditions. This composite adsorbent has a weak ability to resist interference from impurity ions and is difficult to adapt to the complex environmental ions in actual low-concentration rare earth wastewater.

[0006] CN108786712 A discloses a novel magnetic material for selectively adsorbing rare earth ions and its preparation method. First, a silicon source is introduced onto the surface of nano-ferroferric oxide; secondly, a tripod ligand for selectively capturing rare earth ions is synthesized, and finally the tripod ligand is grafted onto the surface of the nanomaterial. The adsorption capacity of this magnetic material for lanthanum ions needs to be improved, and the selectivity in a mixed solution of multiple rare earth ions has not been further explored.

[0007] In summary, the existing adsorbents can achieve the purpose of adsorbing and simply separating rare earth ions, but it is difficult to cope with the complex types of interfering ions and high concentrations of interfering ions in actual application scenarios. Therefore, there is an urgent need to develop a novel composite material and its preparation method that can achieve efficient and selective adsorption of low-concentration rare earth ions. Summary of the Invention

[0008] To solve the above technical problems, the present invention provides a mesoporous composite material, its preparation method and application. The mesoporous composite material exhibits excellent adsorption capacity for rare earth ions in low-concentration rare earth wastewater and has high selectivity, solving the problems of poor adsorption effect and low selectivity of traditional adsorbents in actual application scenarios due to complex types of interfering ions and high concentrations, and realizing the efficient recovery of rare earth resources in low-concentration rare earth wastewater.

[0009] To achieve this purpose, the present invention adopts the following technical solutions:

[0010] In the first aspect, the present invention provides a mesoporous composite material. The mesoporous composite material has a spherical yolk-shell structure, and the spherical yolk-shell structure includes a core, a shell located outside the core, and a cavity formed between the core and the shell. The core includes metal phosphate, and the shell includes mesoporous silica.

[0011] In the mesoporous composite material of the present invention, a metal phosphate is used as the core (i.e., the yolk), and mesoporous silica is used as the shell (i.e., the eggshell), forming a spherical yolk-shell structure with a cavity. The morphology is regular and the structure is adjustable, having a nano-confinement effect, increasing the specific surface area and active sites; among them, the metal phosphate core is the active center, and the mesoporous silica shell provides a stable reaction environment and a rapid mass transfer channel, while the cavity between the yolk and the eggshell provides a buffering effect for the metal phosphate core, preventing the structure from cracking due to volume expansion during the reaction and reducing the active centers; at the same time, the presence of the cavity further improves the mass transfer efficiency, facilitating the easier contact of rare earth ions with the metal phosphate active centers; therefore, the metal phosphate core, the cavity and the mesoporous silica shell act synergistically to jointly improve the adsorption capacity and selectivity of the mesoporous composite material for low-concentration rare earth ions.

[0012] Preferably, the particle size of the mesoporous composite material is 400 - 800 nm, for example, it can be 400 nm, 500 nm, 600 nm, 700 nm or 800 nm, etc.

[0013] Preferably, the specific surface area of the mesoporous composite material is 100 - 200 m 2 / g, for example, it can be 100 m 2 / g, 120 m 2 / g, 150 m 2 / g, 180 m 2 / g or 200 m 2 / g, etc.

[0014] Preferably, the diameter of the core in the mesoporous composite material is 100 - 400 nm, for example, it can be 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm or 400 nm, etc.

[0015] Preferably, the thickness of the shell in the mesoporous composite material is 50 - 100 nm, for example, it can be 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, etc.

[0016] Preferably, the thickness of the cavity is 300 - 700 nm, for example, it can be 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm or 700 nm, etc.

[0017] The present invention further preferably has the thickness of the cavity being 300-700 nm, which is beneficial to fully exert the nano-confinement effect, increase the specific surface area and active sites of the mesoporous composite material, and improve the high-efficiency selective adsorption of rare earth ions. If the thickness of the cavity is relatively thick, it will cause the rare earth ions not to be in full contact with the phosphate kernel, resulting in poor adsorption performance of the mesoporous composite material. If the thickness of the cavity is relatively thin, it will lead to a lower specific surface area of the mesoporous composite material, thus affecting the adsorption effect on rare earth ions.

[0018] Preferably, the mesopore diameter of the mesoporous silica is 1-3 nm, and for example, it can be 1 nm, 1.2 nm, 1.5 nm, 2 nm, 2.2 nm, 2.5 nm, 2.8 nm or 3 nm, etc.

[0019] In a second aspect, the present invention provides a preparation method of the mesoporous composite material described in the first aspect. The preparation method includes the following steps:

[0020] (1) Mix the metal phosphate, carbon source and solvent for a first reaction, and then perform solid-liquid separation to obtain a first solid phase; the first solid phase is subjected to a first calcination in an inert atmosphere to obtain a second solid phase;

[0021] (2) Mix the second solid phase obtained in step (1), the silicon source and the surfactant for a second reaction, and then perform solid-liquid separation to obtain a third solid phase; the third solid phase is subjected to a second calcination in an oxygen-containing atmosphere to obtain the mesoporous composite material.

[0022] In the preparation method of the mesoporous composite material provided by the present invention, the metal phosphate and the carbon source are subjected to a first reaction and a first calcination in an inert atmosphere to obtain a second solid phase, that is, a carbon-layer-wrapped metal phosphate composite material. Then, the silicon source and the surfactant are used to react with the second solid phase, and the carbon layer on the surface of the metal phosphate composite material is removed by a second calcination in an oxygen-containing atmosphere, while forming a mesoporous silica shell, successfully preparing a mesoporous composite material with a nano-confinement effect, which has a spherical yolk-shell structure with a cavity, with a metal phosphate as the kernel and mesoporous silica as the shell, and has a high selective adsorption effect on rare earth ions in low-concentration rare earth wastewater. The preparation method has a simple process flow and low cost.

[0023] Preferably, the mass ratio of the metal phosphate to the carbon source in step (1) is 1:(10-90), and for example, it can be 1:10, 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80 or 1:90, preferably 1:(20-70), etc.

[0024] The present invention further preferably has a mass ratio of the metal phosphate to the carbon source of 1:(20 - 70), which is conducive to ensuring an appropriate carbon layer thickness of the second solid phase, i.e., the metal phosphate composite material wrapped by the carbon layer, conducive to ensuring the thickness of the cavity in the yolk-shell structure subsequently, thereby ensuring the large specific surface area and high active sites of the obtained mesoporous composite material, and improving the selective adsorption ability for rare earth ions; if the mass ratio of the metal phosphate to the carbon source is too low, it will lead to a thinner cavity in the subsequent mesoporous composite material, resulting in a weakened selective adsorption ability for rare earth ions; if the mass ratio of the metal phosphate to the carbon source is too high, it will lead to a thicker cavity in the subsequent mesoporous composite material, resulting in insufficient contact between rare earth ions and the active center of the metal phosphate, thus leading to a weakened selective adsorption ability for rare earth ions.

[0025] Preferably, the phosphate in the metal phosphate in step (1) includes any one or at least two combinations of hydrogen phosphate, dihydrogen phosphate or orthophosphate; typical but non-limiting combinations include the combination of hydrogen phosphate and dihydrogen phosphate, the combination of dihydrogen phosphate and orthophosphate, or the combination of hydrogen phosphate and orthophosphate, etc.

[0026] Preferably, the metal in the metal phosphate in step (1) includes any one or at least two combinations of aluminum, magnesium, calcium, iron, zirconium, cobalt, copper or zinc, and typical but non-limiting combinations include the combination of aluminum and magnesium, the combination of magnesium and calcium, the combination of iron, zirconium, cobalt or copper, or the combination of copper or zinc, etc.

[0027] Preferably, the carbon source in step (1) includes resorcinol and formaldehyde.

[0028] Preferably, the mass ratio of resorcinol to formaldehyde is 1:(1 - 3), for example, it can be 1:1, 1:1.5, 1:2, 1:2.5 or 1:3, etc.

[0029] Preferably, a first auxiliary agent is further added during the mixing process in step (1);

[0030] Preferably, the first auxiliary agent includes ammonia water.

[0031] Preferably, the mass ratio of the metal phosphate to the first auxiliary agent in step (1) is 1:(30 - 50), for example, it can be 1:30, 1:32, 1:35, 1:38, 1:40, 1:42, 1:45, 1:48 or 1:50, etc.

[0032] Preferably, the mass ratio of the metal phosphate to the solvent in step (1) is 1:(900 - 1200), for example, it can be 1:900, 1:950, 1:1000, 1:1050, 1:1100, 1:1150 or 1:1200, etc.

[0033] Preferably, the solvent in step (1) includes ethanol and / or water.

[0034] Preferably, during the first reaction in step (1), ultrasonic treatment and first stirring are carried out successively.

[0035] Preferably, the time of ultrasonic treatment is 0.1 - 1 h, for example, it can be 0.1 h, 0.2 h, 0.3 h, 0.4 h, 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h or 1 h, etc.

[0036] Preferably, the rotation speed of the first stirring is 300 - 1000 rpm, for example, it can be 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm or 1000 rpm, etc., and preferably 500 - 800 rpm.

[0037] Preferably, the time of the first stirring is 6 - 24 h, for example, it can be 6 h, 8 h, 10 h, 12 h, 15 h, 18 h, 20 h, 22 h or 24 h, etc.

[0038] The preparation method of the present invention further preferably includes successively carried out ultrasonic treatment and first stirring during the first reaction in step (1); and further preferably, the time of ultrasonic treatment is 0.1 - 1 h; the rotation speed of the first stirring is 500 - 800 rpm, and the time is 6 - 24 h; which is beneficial to the full progress of the first reaction, successfully preparing the metal phosphate coated with a carbon layer, and combining with step (2) to ensure the successful acquisition of the cavity structure of the mesoporous composite material, thereby ensuring the efficient selective adsorption of rare earth ions.

[0039] Preferably, after the solid-liquid separation in step (1), the first solid phase is further subjected to first washing and first drying.

[0040] Preferably, the temperature of the first drying is 60 - 100 °C, for example, it can be 60 °C, 70 °C, 80 °C, 90 °C or 100 °C, etc.

[0041] Preferably, the time of the first drying is 6 - 12 h, for example, it can be 6 h, 7 h, 8 h, 9 h, 10 h, 11 h or 12 h, etc.

[0042] Preferably, the inert gas in the inert atmosphere in step (1) includes nitrogen and / or argon.

[0043] Preferably, the temperature of the first calcination in step (1) is 400 - 800 °C, for example, it can be 400 °C, 450 °C, 500 °C, 550 °C, 600 °C, 650 °C, 700 °C, 750 °C or 800 °C, etc.

[0044] Preferably, the time of the first calcination in step (1) is 0.5 to 6 h, for example, it can be 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h or 6 h, etc.

[0045] Preferably, the mass ratio of the second solid phase to the silicon source in step (2) is 1:(3 - 5), for example, it can be 1:3, 1:3.2, 1:3.5, 1:3.8, 1:4, 1:4.2, 1:4.5, 1:4.8 or 1:5, etc.

[0046] The present invention further preferably has the mass ratio of the second solid phase to the silicon source in step (2) as 1:(3 - 5) to control the mass ratio of metal phosphate to mesoporous silica in the mesoporous composite material within an appropriate range, thereby improving the selective adsorption effect of the mesoporous composite material on rare earth ions; if the mass ratio of the second solid phase to the silicon source in step (2) is too small, it will lead to fewer active centers and it is difficult for rare earth ions to contact with metal phosphate, resulting in poor adsorption effect; if the mass ratio of the second solid phase to the silicon source in step (2) is too large, it will lead to a thinner shell of the mesoporous composite material and unstable structure, resulting in poor adsorption effect.

[0047] Preferably, the silicon source in step (2) includes tetraethyl orthosilicate, etc.

[0048] Preferably, the mass ratio of the second solid phase to the surfactant in step (2) is 1:(0.1 - 50), for example, it can be 1:0.1, 1:5, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45 or 1:50, etc.

[0049] Preferably, the surfactant in step (2) includes cetyltrimethylammonium bromide.

[0050] Preferably, a second auxiliary agent is also added during the mixing process in step (2).

[0051] Preferably, the mass ratio of the second solid phase to the second auxiliary agent in step (2) is 1:(10 - 50), for example, it can be 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45 or 1:50, etc.

[0052] Preferably, the second auxiliary agent in step (2) includes ammonia water.

[0053] Preferably, the mass fraction of NH3 in the ammonia water of the second auxiliary agent in step (2) is 20 - 30 wt%, for example, it can be 20 wt%, 22 wt%, 25 wt%, 28 wt% or 30 wt%, etc.

[0054] Preferably, the second reaction in step (2) is accompanied by second stirring.

[0055] Preferably, the rotation speed of the second stirring is 300 - 1000 rpm, for example, it can be 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm or 1000 rpm, etc., and preferably 500 - 800 rpm.

[0056] Preferably, the time of the second stirring is 0.5 - 6 h, for example, it can be 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h or 6 h, etc.

[0057] Preferably, after the solid-liquid separation in step (2), the third solid phase is further subjected to second washing and second drying in sequence.

[0058] Preferably, the temperature of the second drying is 60 - 100 °C, for example, it can be 60 °C, 70 °C, 80 °C, 90 °C or 100 °C, etc.

[0059] Preferably, the time of the second drying is 6 - 12 h, for example, it can be 6 h, 7 h, 8 h, 9 h, 10 h, 11 h or 12 h, etc.

[0060] Preferably, the temperature of the second calcination in step (2) is 400 - 800 °C, for example, it can be 400 °C, 450 °C, 500 °C, 550 °C, 600 °C, 650 °C, 700 °C, 750 °C or 800 °C, etc.

[0061] Preferably, the time of the second calcination in step (2) is 4 - 16 h, for example, it can be 4 h, 6 h, 8 h, 10 h, 12 h, 14 h or 16 h, etc.

[0062] Preferably, the oxygen-containing atmosphere in step (2) includes air and / or oxygen.

[0063] As a further preferred technical solution of the present invention, the preparation method includes the following steps:

[0064] (1) Mix metal phosphate, carbon source, first auxiliary agent and solvent in a mass ratio of 1:(10 - 90):(30 - 50):(900 - 1200) for the first reaction. The process of the first reaction includes: first ultrasonic for 0.1 - 1 h, and then first stir at a rotation speed of 300 - 1000 rpm for 6 - 24 h; then perform solid-liquid separation to obtain the first solid phase; the first solid phase is first calcined in an inert atmosphere at 400 - 800 °C for 0.5 - 6 h to obtain the second solid phase;

[0065] The phosphate in the metal phosphate includes any one or a combination of at least two of hydrogen phosphate, dihydrogen phosphate or orthophosphate; the metal in the metal phosphate includes any one or a combination of at least two of aluminum, magnesium, calcium, iron, zirconium, cobalt, copper or zinc; the carbon source includes resorcinol and formaldehyde with a mass ratio of 1:(1-3); the first auxiliary agent includes ammonia water; the inert gas in the inert atmosphere includes nitrogen and / or argon;

[0066] (2) Mix the second solid phase, silicon source, surfactant and second auxiliary agent described in step (1) in a ratio of 1:(3-5):(0.1-50):(10-50) for a second reaction. During the second reaction, stir second at a speed of 300-1000 rpm for 0.5-6 h; then perform solid-liquid separation to obtain a third solid phase; the third solid phase is second calcined in an oxygen-containing atmosphere at 400-800 °C for 4-16 h to obtain the mesoporous composite material;

[0067] The silicon source includes tetraethyl orthosilicate; the surfactant includes cetyltrimethylammonium bromide; the second auxiliary agent includes ammonia water; the oxygen-containing atmosphere includes air and / or oxygen.

[0068] Thirdly, the present invention provides an application of the mesoporous composite material described in the first aspect, and the mesoporous composite material is used for selectively adsorbing rare earth ions.

[0069] Due to the nano-confinement effect, high specific surface area and abundant active sites of the mesoporous composite material described in the first aspect of the present invention with a yolk-shell structure having a cavity, it shows high adsorption capacity and high selectivity for rare earth ions in rare earth wastewater, can adapt to the actual application environment of rare earth wastewater with complex and high-concentration interfering ion species, is suitable for the efficient selective adsorption and resource recovery of low-concentration rare earth ions, and has good application prospects for the high-value extraction and separation of various rare earth ions in rare earth wastewater.

[0070] Compared with the prior art, the present invention has at least the following beneficial effects:

[0071] (1) The mesoporous composite material provided by the present invention has a nano-confinement effect. It uses metal phosphate as the core (i.e., yolk) and mesoporous silica as the shell (i.e., eggshell) to form a spherical yolk-shell structure with a cavity. It has regular morphology and adjustable structure, high specific surface area and abundant active sites, has a high adsorption rate for rare earth ions in low-concentration rare earth wastewater, and shows high selectivity for Sm 3+ and Eu 3+ and shows high selectivity for Sm 3+ and Eu 3+ The distribution coefficients of and are about 1.4-6.7 times higher than those of other interfering ions.

[0072] (2) The preparation method of the mesoporous composite material provided by the present invention uses the metal phosphate and carbon source to obtain a second solid phase through a first reaction and a first calcination. The second solid phase is a metal phosphate composite material wrapped by a carbon layer. Then, a silicon source and a surfactant are used to react with the second solid phase to remove the carbon layer on the surface of the metal phosphate composite material and simultaneously form a mesoporous silica shell. By controlling the raw material mass ratio, temperature, time and other parameters of each step, a mesoporous composite material with a nano-confinement effect is successfully prepared. The preparation method has a simple process flow and low cost, and is suitable for large-scale industrial production.

[0073] (3) The application of the mesoporous composite material provided by the present invention. Due to its nano-confinement effect of a spherical yolk-shell structure with a cavity, high specific surface area and abundant active sites, the mesoporous composite material can adapt to the actual application environment of rare earth wastewater with complex and high-concentration interfering ion species, and has good application prospects for the extraction and separation of various rare earth ions from rare earth wastewater. Description of the Drawings

[0074] Figure 1 is the SEM image of the mesoporous composite material obtained in Example 1 of the present invention;

[0075] Figure 2 is the TEM image of the mesoporous composite material obtained in Example 1 of the present invention;

[0076] Figure 3 is the nuclear magnetic resonance image of phosphorus element of the mesoporous composite material obtained in Example 1 of the present invention and the aluminum phosphate material obtained in Comparative Example 2;

[0077] Figure 4 is the adsorption experiment image of the mesoporous composite material obtained in Example 1 of the present invention for different rare earth ions;

[0078] Figure 5 is the adsorption experiment image of the mesoporous composite material obtained in Comparative Example 2 of the present invention for different rare earth ions;

[0079] Figure 6 is the adsorption experiment image of the mesoporous composite material obtained in Comparative Example 3 of the present invention for different rare earth ions. Detailed Embodiments

[0080] The technical solution of the present invention will be further described below with reference to the drawings and through specific embodiments. However, the following examples are only simple examples of the present invention and do not represent or limit the scope of the protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0081] As a specific embodiment of the present invention, the preparation method of the mesoporous composite material includes the following steps:

[0082] (1) Mix metal phosphate, carbon source, first auxiliary agent and solvent in a ratio of 1:(10 - 90):(30 - 50):(900 - 1200) to conduct the first reaction. The process of the first reaction includes: first ultrasonicate for 0.1 - 1 h, and then first stir at a speed of 300 - 1000 rpm for 6 - 24 h; then perform solid-liquid separation to obtain the first solid phase; after the first solid phase is first washed, first dry it at 60 - 100 °C for 6 - 12 h, and then first calcine it at 400 - 800 °C in an inert atmosphere for 0.5 - 6 h to obtain the second solid phase;

[0083] The phosphate in the metal phosphate includes any one or at least two combinations of hydrogen phosphate, dihydrogen phosphate or orthophosphate; the metal in the metal phosphate includes any one or at least two combinations of aluminum, magnesium, calcium, iron, zirconium, cobalt, copper or zinc; the carbon source includes resorcinol and formaldehyde with a mass ratio of 1:(1 - 3); the first auxiliary agent includes ammonia water; the inert gas in the inert atmosphere includes nitrogen and / or argon;

[0084] (2) Mix the second solid phase obtained in step (1), silicon source, surfactant and second auxiliary agent in a ratio of 1:(3 - 5):(0.1 - 50):(10 - 50) to conduct the second reaction. During the process of the second reaction, second stir at a speed of 300 - 1000 rpm for 0.5 - 6 h; then perform solid-liquid separation to obtain the third solid phase; after the third solid phase is second washed, first dry it at 60 - 100 °C for 6 - 12 h, and then second calcine it at 400 - 800 °C in an oxygen-containing atmosphere for 4 - 16 h to obtain the mesoporous composite material;

[0085] The silicon source includes tetraethyl orthosilicate; the surfactant includes cetyltrimethylammonium bromide; the second auxiliary agent includes ammonia water; the oxygen-containing atmosphere includes air and / or oxygen.

[0086] I. Examples

[0087] Example 1

[0088] This example provides a preparation method of a mesoporous composite material. The preparation method includes the following steps:

[0089] (1) Mix aluminum phosphate, resorcinol, formaldehyde (37.5 wt%), ammonia water (25 wt%) and ethanol in a ratio of 1:10:20:40:1000 to conduct the first reaction. The process of the first reaction includes: first ultrasonicate for 0.5 h, and then first stir at a speed of 600 rpm for 18 h; then filter to obtain the first solid phase; after the first solid phase is first washed, first dry it at 80 °C for 10 h, and then first calcine it at 600 °C in an argon atmosphere for 4 h to obtain the second solid phase;

[0090] (2) The second solid phase, tetraethyl orthosilicate, cetyltrimethylammonium bromide, and ammonia water (25 wt%) described in step (1) are mixed in a mass ratio of 1:4:10:20 for a second reaction. During the second reaction, stirring is carried out at a speed of 600 rpm for 3 h; then, filtration is carried out to obtain a third solid phase; the third solid phase is washed a second time and then dried at 80 °C for 9 h and then calcined at 600 °C in an air atmosphere for 6 h to obtain the mesoporous composite material.

[0091] As Figure 1 and Figure 2 shown, the mesoporous composite material obtained in this example has a spherical yolk-shell structure. The spherical yolk-shell structure includes a core, a shell located outside the core, and a cavity formed between the core and the shell. The thickness of the cavity is 500 nm. The core includes aluminum phosphate, and the diameter of the core is 200 nm. The shell includes mesoporous silica, and the thickness of the shell is 80 nm and the mesopore diameter is 2 nm. The particle size of the mesoporous composite material is 780 nm and the specific surface area is 180 m 2 / g.

[0092] In addition, according to Figure 3 it can be known that there are obvious differences in the phosphorus nuclear magnetic resonance spectra of the mesoporous composite material obtained in this example and the aluminum phosphate material obtained in Comparative Example 2, indicating that the phosphate groups in the mesoporous composite material obtained in this example exist in multiple forms, including PO4 3- , HPO4 2- and H2PO4 - .

[0093] As Figure 4 shown, the mesoporous composite material obtained in this example shows excellent adsorption effects and high selectivity for Sm 3+ and Eu 3+ , is very little affected by other interfering ions in the solution, and can achieve efficient extraction and separation of rare earth ions from low-concentration rare earth wastewater.

[0094] Example 2

[0095] This example provides a preparation method of a mesoporous composite material. The preparation method includes the following steps:

[0096] (1) Mix aluminum phosphate, resorcinol, formaldehyde (36.5 wt%), ammonia water (20 wt%) and ethanol in a mass ratio of 1:10:10:30:900 for the first reaction. The process of the first reaction includes: first, ultrasonicate for 0.3 h, and then stir at a speed of 500 rpm for 24 h; then filter to obtain a first solid phase; after the first solid phase is first washed, first dry at 60 °C for 12 h, and then first calcine at 400 °C in a nitrogen atmosphere for 6 h to obtain a second solid phase;

[0097] (2) Mix the second solid phase obtained in step (1), tetraethyl orthosilicate, cetyltrimethylammonium bromide and ammonia water (20 wt%) in a mass ratio of 1:3:20:10 for the second reaction. During the second reaction, stir at a speed of 500 rpm for 6 h; then filter to obtain a third solid phase; after the third solid phase is second washed, first dry at 60 °C for 12 h, and then second calcine at 400 °C in an air atmosphere for 16 h to obtain the mesoporous composite material.

[0098] The mesoporous composite material obtained in this example has a spherical yolk-shell structure. The spherical yolk-shell structure includes a core, a shell located outside the core, and a cavity formed between the core and the shell. The thickness of the cavity is 300 nm. The core includes iron phosphate, and the diameter of the core is 100 nm. The shell includes mesoporous silica, and the thickness of the shell is 300 nm and the mesopore diameter is 1 nm. The particle size of the mesoporous composite material is 700 nm and the specific surface area is 120 m 2 / g.

[0099] The mesoporous adsorbent material obtained in this example has an efficient and selective adsorption effect on Sm 3+ and Eu 3+ which is equivalent to that of Example 1.

[0100] Example 3

[0101] This example provides a method for preparing a mesoporous composite material. The preparation method includes the following steps:

[0102] (1) Mix magnesium phosphate, resorcinol, formaldehyde (38 wt%), ammonia water (30 wt%) and ethanol in a mass ratio of 1:30:40:50:1200 for the first reaction. The process of the first reaction includes: first, ultrasonicate for 1 h, and then stir at a speed of 800 rpm for 10 h; then filter to obtain a first solid phase; after the first solid phase is first washed, first dry at 100 °C for 6 h, and then first calcine at 800 °C in an argon atmosphere for 3 h to obtain a second solid phase;

[0103] (2) The second solid phase, tetraethyl orthosilicate, cetyltrimethylammonium bromide, and ammonia water (30 wt%) described in step (1) are mixed in a ratio of 1:5:30:50 for a second reaction. During the second reaction, it is second stirred at a speed of 800 rpm for 3 h; then it is filtered to obtain a third solid phase; the third solid phase is second washed and then second dried at 100 °C for 6 h, and then second calcined at 800 °C in an air atmosphere for 8 h to obtain the mesoporous composite material.

[0104] The mesoporous composite material obtained in this example has a spherical yolk-shell structure. The spherical yolk-shell structure includes a core, a shell located outside the core, and a cavity formed between the core and the shell. The thickness of the cavity is 500 nm. The core includes magnesium phosphate, and the diameter of the core is 200 nm. The shell includes mesoporous silica, and the thickness of the shell is 60 nm and the mesopore diameter is 2.5 nm. The particle size of the mesoporous composite material is 760 nm and the specific surface area is 170 m 2 / g.

[0105] The mesoporous adsorption material obtained in this example has an efficient selective adsorption effect on Sm 3+ and Eu 3+ which is equivalent to the selective adsorption effects of Example 1 and Example 2.

[0106] Example 4

[0107] This example provides a preparation method of a mesoporous composite material. Except that the mass ratio of the aluminum phosphate described in step (1) to the sum of the masses of the resorcinol and formaldehyde is 1:10, the rest are the same as in Example 1.

[0108] Example 5

[0109] This example provides a preparation method of a mesoporous composite material. Except that the mass ratio of the aluminum phosphate described in step (1) to the sum of the masses of the resorcinol and formaldehyde is 1:90, the rest are the same as in Example 1.

[0110] Since the mass ratio of the aluminum phosphate to the carbon source (resorcinol and formaldehyde) in Example 4 is relatively high, that is, the sum of the masses of the resorcinol and formaldehyde is relatively small, the cavity prepared subsequently is relatively thin, resulting in an increase in the adsorption capacity of the obtained mesoporous adsorption material for Er 3+ and Y 3+ and an increase in the adsorption of Sm 3+ and Eu 3+The efficient selective adsorption ability decreases; since the mass ratio of the aluminum phosphate to the carbon source (resorcinol and formaldehyde) described in Example 5 is low, that is, the sum of the masses of resorcinol and formaldehyde is high, it will lead to a relatively thick cavity of the subsequent mesoporous composite material, resulting in insufficient contact between rare earth ions and the metal phosphate active center, poor adsorption effect on rare earth ions, and poor adsorption effect on Sm 3+ and Eu 3+ The efficient selective adsorption ability decreases; this shows that the present invention further preferably selects the mass ratio of the metal phosphate to the carbon source in step (1) to be 1: (20-70), further improving the adsorption rate of the obtained mesoporous composite material to rare earth ions and the selective adsorption effect on Sm 3+ and Eu 3+ The selective adsorption effect.

[0111] Example 6

[0112] This example provides a method for preparing a mesoporous composite material. Except that the mass ratio of the second solid phase to tetraethyl orthosilicate in step (2) is 1:2.5, the rest are the same as in Example 1.

[0113] Example 7

[0114] This example provides a method for preparing a mesoporous composite material. Except that the mass ratio of the second solid phase to tetraethyl orthosilicate in step (2) is 1:5.5, the rest are the same as in Example 1.

[0115] Since the mass ratio of the second solid phase to tetraethyl orthosilicate in Example 6 is large, that is, the mass of tetraethyl orthosilicate is low, resulting in a relatively thin outer shell of the mesoporous composite material and unstable structure, resulting in poor selective adsorption ability of the obtained mesoporous composite material to rare earth ions; since the mass ratio of the second solid phase to tetraethyl orthosilicate in Example 7 is small, that is, the mass of tetraethyl orthosilicate is large, resulting in fewer active centers and difficulty for rare earth ions to contact the metal phosphate, thus resulting in poor adsorption effect of the obtained mesoporous composite material on rare earth ions; this shows that the present invention further preferably selects the mass ratio of the second solid phase to the silicon source in step (2) to be 1: (3-5), further improving the adsorption rate of the obtained mesoporous composite material to rare earth ions and the selective adsorption effect on Sm 3+ and Eu 3+ The selective adsorption effect.

[0116] II. Comparative Examples

[0117] Comparative Example 1

[0118] This comparative example provides a method for preparing a mesoporous composite material. Except that resorcinol and formaldehyde are not mixed in step (1), the rest are the same as in Example 1.

[0119] The mesoporous composite material obtained in this comparative example has a core-shell structure and no cavity, resulting in a decrease in the mass transfer rate, and thus a poor adsorption effect of the mesoporous composite material on rare earth ions in rare earth wastewater.

[0120] Comparative Example 2

[0121] This comparative example provides a preparation method of an aluminum phosphate material, and the preparation method includes: sequentially washing, drying for the first time, calcining for the first time, washing for the second time, drying for the second time, and calcining for the second time for the aluminum phosphate, and the parameters are the same as those in Example 1.

[0122] Comparative Example 3

[0123] This comparative example provides a preparation method of a mesoporous silica material. Except that step (1) is not carried out but step (2) is directly carried out, and the raw materials for mixing in step (2) do not include the second solid phase, the rest are the same as those in Example 1.

[0124] Since Comparative Example 2 and Comparative Example 3 are a single aluminum phosphate material and a mesoporous silica material respectively, there is no synergistic effect. Although there is a certain selective adsorption effect, the adsorption rates of the two on rare earth ions are significantly worse. Among them, the adsorption effect of the mesoporous silica material in Comparative Example 3 on rare earth ions is almost nil; this shows that the spherical yolk-shell structure with a cavity of the mesoporous composite material of the present invention, with metal phosphate as the inner core and mesoporous silica as the outer shell, through synergistic action, makes its adsorption effect on rare earth ions very excellent, and also shows high selective adsorption for Sm 3+ and Eu 3+ .

[0125] Comparative Example 4

[0126] This comparative example provides a preparation method of a mesoporous composite material. Except that the first calcination in step (1) is carried out in an air atmosphere, the rest are the same as those in Example 1.

[0127] Comparative Example 5

[0128] This comparative example provides a preparation method of a mesoporous composite material. Except that the second calcination in step (2) is carried out in an argon atmosphere, the rest are the same as those in Example 1.

[0129] Since the first calcination in Comparative Example 4 is not carried out in an inert gas atmosphere, the formation of a cavity is not possible, resulting in a poor selective adsorption effect of the obtained material; since the second calcination in Comparative Example 5 is not carried out in an oxygen-containing atmosphere, the obtained material cannot form mesopores and cavities, and cannot form a spherical yolk-shell structure, resulting in a poor selective adsorption effect on rare earth ions.

[0130] III. Tests and Results

[0131] ① Test method

[0132] Weigh 10 mg of the materials prepared in the above-mentioned examples and comparative examples respectively, and place them in a conical flask. Add 10 mL of a mixed rare earth ion solution containing 1 mg / L of lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu), and yttrium (Y) into the conical flask. Ultrasonic for 30 s in an ultrasonic cleaner, and then shake on a constant temperature shaker with an oscillation rate of 150 rpm for 12 h. After sampling and filtering the solution in the conical flask, use an ICP-MS instrument to detect the remaining rare earth ion concentration in the solution.

[0133] ② Test results

[0134] According to the above test method, test and draw the distribution coefficient diagrams of the rare earth ions in the solution for the materials obtained in Example 1, Comparative Example 2, and Comparative Example 3. The results are as Figures 4 to 6 shown;

[0135] Comparison Figures 4 to 6 As shown, it can be seen that the mesoporous composite material described in the present invention shows excellent adsorption effect and high selectivity for Sm 3+ and Eu 3+ and is hardly affected by other interfering ions in the solution; while the materials provided in Comparative Example 2 and Comparative Example 3 have poor adsorption effect on rare earth ions and almost no selectivity.

[0136] In summary, by controlling process parameters such as raw material ratio and calcination atmosphere in the preparation method, the present invention successfully prepares a mesoporous composite material with a spherical yolk-shell structure. The spherical yolk-shell structure includes a core, a shell located outside the core, and a cavity formed between the core and the shell. The core includes metal phosphate, and the shell includes mesoporous silica; the various parts cooperate with each other, enabling it to have excellent high-efficiency selectivity for rare earth ions and capable of realizing the efficient extraction and separation of rare earth ions from low-concentration rare earth wastewater.

[0137] The applicant declares that the above is only the specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention fall within the protection scope and the disclosure scope of the present invention.

Claims

1. A mesoporous composite material, characterized in that, The mesoporous composite material has a spherical yolk-shell structure, which includes a core, a shell located outside the core, and a cavity formed between the core and the shell. The core includes metal phosphate, and the shell includes mesoporous silica.

2. The mesoporous composite material according to claim 1, wherein The particle size of the mesoporous composite material is 400 - 800 nm; Preferably, the specific surface area of the mesoporous composite material is 100 to 200 m 2 / g.

3. The mesoporous composite material according to claim 1 or 2, characterized in that, The diameter of the core in the mesoporous composite material is 100 - 400 nm; Preferably, the thickness of the shell in the mesoporous composite material is 50 - 100 nm; Preferably, the thickness of the cavity is 300 - 700 nm; Preferably, the mesopore diameter of the mesoporous silica is 1 - 3 nm.

4. A method for preparing a mesoporous composite material according to any one of claims 1 to 3, characterized in that, The preparation method includes the following steps: (1) Mix metal phosphate, carbon source and solvent for a first reaction, and then perform solid-liquid separation to obtain a first solid phase; the first solid phase is calcined for the first time in an inert atmosphere to obtain a second solid phase; (2) Mix the second solid phase obtained in step (1), a silicon source and a surfactant for a second reaction, and then perform solid-liquid separation to obtain a third solid phase; the third solid phase is calcined for the second time in an oxygen-containing atmosphere to obtain the mesoporous composite material.

5. The preparation method according to claim 4, characterized in that, The mass ratio of the metal phosphate to the carbon source in step (1) is 1:(10 - 90), preferably 1:(20 - 70); Preferably, the phosphate in the metal phosphate in step (1) includes any one or at least two combinations of hydrogen phosphate, dihydrogen phosphate or orthophosphate; Preferably, the metal in the metal phosphate in step (1) includes any one or at least two combinations of aluminum, magnesium, calcium, iron, zirconium, cobalt, copper or zinc; Preferably, the carbon source in step (1) includes resorcinol and formaldehyde; Preferably, the mass ratio of resorcinol to formaldehyde is 1:(1 - 3); Preferably, a first auxiliary agent is added during the mixing process in step (1); Preferably, the first auxiliary agent includes ammonia water; Preferably, the mass ratio of the metal phosphate to the first auxiliary agent in step (1) is 1:(30 - 50); Preferably, the mass ratio of the metal phosphate to the solvent in step (1) is 1:(900 - 1200).

6. The preparation method according to claim 4 or 5, characterized in that, The first reaction in step (1) includes performing ultrasonic treatment and first stirring in sequence; Preferably, the time of ultrasonic treatment is 0.1 - 1 h; Preferably, the rotation speed of the first stirring is 300 - 1000 rpm, preferably 500 - 800 rpm; Preferably, the time of the first stirring is 6 - 24 h; Preferably, the inert gas in the inert atmosphere in step (1) includes nitrogen and / or argon; Preferably, the temperature of the first calcination in step (1) is 400 - 800 °C; Preferably, the time of the first calcination in step (1) is 0.5 - 6 h.

7. The preparation method according to any one of claims 4 to 6, characterized in that, The mass ratio of the second solid phase to the silicon source in step (2) is 1:(3 - 5); Preferably, the silicon source in step (2) includes tetraethyl orthosilicate; Preferably, the mass ratio of the second solid phase to the surfactant in step (2) is 1:(0.1 - 50); Preferably, the surfactant in step (2) includes cetyltrimethylammonium bromide; Preferably, a second auxiliary agent is further added during the mixing in step (2); Preferably, the mass ratio of the second solid phase to the second auxiliary agent in step (2) is 1:(10 - 50); Preferably, the second auxiliary agent in step (2) includes ammonia water.

8. The preparation method according to any one of claims 4 to 7, characterized in that, A second stirring is carried out during the second reaction in step (2); Preferably, the rotation speed of the second stirring is 300 - 1000 rpm, preferably 500 - 800 rpm; Preferably, the time of the second stirring is 0.5 - 6 h; Preferably, the temperature of the second calcination in step (2) is 400 - 800 °C; Preferably, the time of the second calcination in step (2) is 4 - 16 h; Preferably, the oxygen-containing atmosphere in step (2) includes air and / or oxygen.

9. The preparation method according to any one of claims 4 to 8, characterized in that, The preparation method includes the following steps: (1) Mix metal phosphate, carbon source, first auxiliary agent and solvent in a mass ratio of 1:(10 - 90):(30 - 50):(900 - 1200) to carry out a first reaction. The first reaction process includes: first ultrasonic for 0.1 - 1 h, and then first stir at a rotation speed of 300 - 1000 rpm for 6 - 24 h; then carry out solid-liquid separation to obtain a first solid phase; the first solid phase is first calcined in an inert atmosphere at 400 - 800 °C for 0.5 - 6 h to obtain a second solid phase; The phosphate in the metal phosphate includes any one or at least two combinations of hydrogen phosphate, dihydrogen phosphate or orthophosphate; the metal in the metal phosphate includes any one or at least two combinations of aluminum, magnesium, calcium, iron, zirconium, cobalt, copper or zinc; the carbon source includes resorcinol and formaldehyde with a mass ratio of 1:(1 - 3); the first auxiliary agent includes ammonia water; the inert gas in the inert atmosphere includes nitrogen and / or argon; (2) Mix the second solid phase, silicon source, surfactant and second auxiliary agent in step (1) in a mass ratio of 1:(3 - 5):(0.1 - 50):(10 - 50) to carry out a second reaction. During the second reaction process, stir at a rotation speed of 300 - 1000 rpm for 0.5 - 6 h; then carry out solid-liquid separation to obtain a third solid phase; the third solid phase is second calcined in an oxygen-containing atmosphere at 400 - 800 °C for 4 - 16 h to obtain the mesoporous composite material; The silicon source includes tetraethyl orthosilicate; the surfactant includes cetyltrimethylammonium bromide; the second auxiliary agent includes ammonia water; the oxygen-containing atmosphere includes air and / or oxygen.

10. Use of a mesoporous composite material according to any one of claims 1 to 3, characterized in that, The mesoporous composite material is used for selectively adsorbing rare earth ions.

Citation Information

Patent Citations

  • Novel magnetic material for selective absorption of rare earth ions, and preparation method of novel magnetic material

    CN108786712A